The effect of acoustic information of lexical tones on non-native listeners’ tonal identifications - So, Connie Kwok Lai (Canadian Acoustics, 2003)
The role of acoustic information in the perception training of Mandarin tones was examined. The results indicate that using acoustic information as feedback during a short-span training significantly improves listeners’ performance in tonal identifications, and that the pattern of improvement was consistently observed for each lexical tone. A further examination in listeners’ speech productions would be desirable to find out if these learners were able to produce the tones according to the acoustic information that they have received during training.